A novel method of medium effect for loading incident wave in hybrid ray-tracing/FDTD algorithm. Issue 2 (17th February 2022) - Yuan, Guoxuan; Liu, Yuanjian; Li, Shuangde; Liang, Jingyi
ABSTRACT: A novel method has been proposed in this paper, which is going to combine the reflection, transmission, and diffraction of electromagnetic waves as one phenomenon – medium effect. Based on medium effect, medium separation method is proposed as a strengthened algorithm for the ray-tracing/FDTD method and as a key to invisibility theory. For the medium effect, obstacles will be considered as controlled sources, and final results are obtained by calculating those controlled sources. Medium separation method will be used as a new interface for hybrid ray-tracing/FDTD algorithm and as a key compensated soft source to realize the theory of perfect invisibility. It can inject any electromagnetic wave into scatterers directly without TF/SF boundary; hence, it is easy to realize the simulation of part of scatterers with finite size, which is illuminated by electromagnetic waves. The medium effect and the method of medium separation are introduced in detail in this paper. Simulation results obtained by medium separation method are in good agreement with the calculation results by traditional FDTD algorithm.